EFESIENSI PEMBAYARAN DIGITAL DENGAN KEMUDAHAN DAN KEAMANAN QRIS MELALUI KEPERCAYAAN SEBAGAI PEMEDIASI - Oktarini, Nik (JMD : Jurnal Riset Manajemen & Bisnis Dewantara, 2025)
This study aims to determine the effect of ease and security of QRIS on the efficiency of digital payments with trust as a mediator. The theories used to support this study are the Diffusion of Innovation (DOI) Theory and the Technology Acceptance Model (TAM) Theory. This study focuses on Denpasar City residents belonging to Gen X and Gen Y who use QRIS in transactions. The research method used in this study is a quantitative approach. The population in this study is all Denpasar City residents belonging to Gen X and Gen Y, whose number is not known for certain, so the sample is calculated using the Lameshow formula with the number of samples obtained being 96 respondents. This study has 7 hypotheses, which will be tested using the Structural Equation Model (SEM) approach based on Partial Least Square (PLS). Based on the results of data analysis, the results of ease of QRIS have a positive and significant effect on the efficiency of digital payments. QRIS security has a positive and insignificant effect on the efficiency of digital payments. Ease of QRIS has a positive and significant effect on trust. QRIS security has a positive and significant effect on trust. Trust has a positive and significant effect on the efficiency of digital payments. Trust mediates the effect of QRIS convenience on digital payment efficiency (partial mediation). Trust mediates the effect of QRIS security on digital payment efficiency (full mediation).